If it's not what You are looking for type in the equation solver your own equation and let us solve it.
100(8x-10)=40(980+100x)
We move all terms to the left:
100(8x-10)-(40(980+100x))=0
We add all the numbers together, and all the variables
100(8x-10)-(40(100x+980))=0
We multiply parentheses
800x-(40(100x+980))-1000=0
We calculate terms in parentheses: -(40(100x+980)), so:We get rid of parentheses
40(100x+980)
We multiply parentheses
4000x+39200
Back to the equation:
-(4000x+39200)
800x-4000x-39200-1000=0
We add all the numbers together, and all the variables
-3200x-40200=0
We move all terms containing x to the left, all other terms to the right
-3200x=40200
x=40200/-3200
x=-12+9/16
| 2x-8=1x+4 | | 2x-13=44 | | (12x+5)=(15x-13) | | –13=d2+ –17 | | -4+b=-4 | | 2x^2/x+x(100-15x)x=5 | | 2n+3+7n=8 | | -2-3x=10x=-2 | | 4(x-1)+11.1=0.7(x-0.4) | | -4(3x-2)+3=-12x+11 | | .15(1.5+p)=11.50 | | 1/2(x+8)+5=-3 | | 4(x-1)+11.1=0.7(x-0.4 | | 2/45=x/135 | | (9x-58)=5 | | q2− 1=1 | | -x3+4x2+27x-90=0 | | 5x+19=9x+35 | | 3x-1=3x=7 | | |4m-5|=19 | | 10x=16=6x-8 | | 0=-x3+4x2-27x-90 | | −2x+9=17 | | 7x−6=x+6(x+5) | | 6/5x−6+9/10x=4+6/5x+3−2/5x | | -3x+2=5x+4 | | 90-(4x+2)=90 | | 4(2+x)=-3x+36 | | 65x−6+910x=4+65x+3−25x | | 9+2a=5-3a-6 | | 4(2+x)=-3x+46 | | r−(−19)=8 |